Self play with parameter sharing in n-player mixed competitive-cooperative games - Skaltsis, George Marios; Shin, Hyo-Sang; Tsourdos, Antonios (American Institute of Aeronautics and Astronautics (AIAA), 2021)
We introduce some parameter sharing multi-agent reinforcement learning schemes, combined with self-play for n-players mixed competitive-cooperative games. Except for the pure self-play scheme, an another one using the best policy, outperform the pure parameter sharing baseline, leading to better exploration of the state space and protecting from the performance deterioration observed with the baseline.
Keywords: Reinforcement Learning; Markov Decision Process; Statistical Distributions; Optimization Algorithm; Multi Agent System; Computer Systems; Value Function; Neural Networks; Mathematical Models; Greedy Algorithm